(untitled) (Research, Society and Development, 2022)
Psidium guajava, commonly known as ’guava’, belongs to the Myrtaceae family and is an alternative to the use of traditional methods of corrosion inhibition. The aim of this study is to anodize titanium in an environmentally friendly Psidium guajava electrolyte in order to improve its anti-corrosion performance. For this purpose, samples of CP (commercially pure) titanium grade 2 were anodized in plant extract based on Psidium guajava, with transient variations of current density (1 and 0.1 mA/cm²) and time (5, 30 and 60 min). Samples were characterized in terms of morphology by SEM (Scanning Electron Microscopy) analysis. The hydrophobicity of oxides was evaluated by the sessile drop method. Anodized samples were analyzed for colorimetry by the CIE L*a*b* method and the electrolyte based on Psidium guajava was analyzed by UV-Vis and cyclic voltammetry, in order to understand the compounds and their behavior in the anodizing process. From the obtained results, the oxides generated through anodization at current density of 0.1 mA/cm² were the ones that presented the best performance. The results obtained at 5 and 30 minutes of anodizing showed very similar results and greater reproducibility compared to the others analyzed, which showed the formation of a barrier-type oxide layer in the samples. In the Psidium guajava electrolyte, it was evidenced the presence of phenolic groups in its composition, which is believed to influence the process of formation of the oxide layer in the anodization process.